Fengshi Gutong Capsule Attenuates Osteoarthritis by Inhibiting MAPK, NF-κB, AP-1, and Akt Pathways - Yao-Xin Gao; Hao-Heng Yu; Chuan He; Ming Li; Dan-Dan Guo; Jun-Jiang Lian; Hai-Jie Yang; Mian Wang; Lei Wang; Zhi-Wei Feng; Bin-Feng Cheng; Bin-Feng Cheng (Frontiers Media S.A., 2018)
Background and purpose: Fengshi Gutong capsule (FSGTC), a traditional herbal formula, has been used clinically in China for the treatment of arthritis. However, the mechanism underlying the therapeutic effects of FSGTC on osteoarthritis (OA) has not been elucidated. The present study investigated the function and mechanisms of FSGTC in rat OA model and interleukin (IL)-1β-stimulated synovial cells.Materials and methods: Rat OA model was established by intra-articular injection containing 4% papain. IL-1β-induced SW982 cells were used as an OA cell model. Safranin-O-Fast green (S-O) and hematoxylin-eosin (HE) stainings were used to observe the changes in cartilage morphology. Enzyme-linked immunosorbent assay (ELISA) and real-time quantitative PCR (qPCR) detected the expression of inflammatory cytokines. In addition, molecular mechanisms were analyzed by Western blot in the OA cell model.Results: FSGTC treatment significantly relieved the degeneration of cartilage and reduced the contents of tumor necrosis factor-α (TNF-α) and IL-6 in the serum in papain-induced OA rats. FSGTC also reduced the protein and mRNA levels of IL-6 and IL-8 in IL-1β-stimulated SW982 cells. Moreover, it inhibited the phosphorylation levels of ERK (extracellular signal-related kinase), JNK (c-Jun N-terminal kinase), p38, Akt (protein kinase B), and c-Jun. It also decreased the extent of IκBα degradation and p65 protein translocation into the nucleus.Conclusion: The current data confirmed the protective effects of FSGTC in the rat and OA cell models. The results suggested that FSGTC reduced the production of inflammatory mediators via restraining the activation of mitogen-activated protein kinases (MAPK), nuclear factor kappa B (NF-κB), activator protein-1 (AP-1), and Akt.